Study protocol of the COMPARE-Interaction study: the impact of maternal comorbid depression and anxiety disorders in the peripartum period on child development - Zietlow, Anna-Lena; Woll, Christian Franz Josef; Nonnenmacher, Nora; Müller, Mitho; Labonte, Verena; Ditzen, Beate; Paulus, Markus; Sodian, Beate; Nater, Urs M.; Herpertz, Sabine; Reck, Corinna (BMJ open, 2022)
Introduction To date, there are only few studies that compare the consequences of peripartum maternal depressive disorders (PD) versus depressive with comorbid anxiety disorders (PDCA) for infant and child development. As comorbidity is associated with greater impairment and symptom severity related to the primary diagnosis, comorbidity in mothers might raise their offspring’s risk of developing internalising or externalising disorders even more than has been noted in conjunction with PD alone. - Methods and analysis This study aims to analyse the impact of parental psychopathology, particularly peripartum depression in mothers with and without comorbid anxiety disorders according to the Diagnostic and Statistical Manual of Mental Disorders (DSM-5) on child cognitive and socioemotional development. Maternal/paternal psychopathology, mother-infant/father-infant interaction and child development are assessed at four measurement points over the first 2 years (T1: 3-4 months postpartum, T2: 12 months postpartum, T3: 18 months postpartum and T4: 24 months postpartum). The mediating role of mother-infant/father-infant interaction and infant stress reactivity in the relationship between PD/PDCA and infant cognitive and socioemotional development will be analysed. In the ongoing study, 174 families (n=58 mothers with PD, n=58 mothers with PDCA and n=58 healthy controls) will be recruited in inpatient and outpatient centres as well as maternity hospitals in Munich and Heidelberg. - Ethics and dissemination This study is implemented in accordance with the current guidelines of the World Medical Association (revised Declaration of Helsinki) and the General Data Protection Regulation of the European Union. The study procedures were approved by the independent ethics committees of the Department of Psychology, Ludwig-Maximilians-University Munich (74_Reck_b) and of the Medical Faculty, University Heidelberg (S-446/2017). Participation is voluntary. A signed written informed consent form must be obtained from each study subject prior to any study-specific procedure. Participants can withdraw from the study at any point in time without giving a reason or being subjected to any future disadvantages. In case of withdrawal from the study, the subject’s data and material will be kept unless the participant asks for data removal. Results will be published and disseminated to further the discussion on the effects of maternal PD and PDCA on parent-infant interaction, infant stress reactivity and child development. Furthermore, study results will be presented at international congresses and expert conferences.
Gesehen am 16.09.2022